Kontribusi Kemandirian Belajar Dan Perhatian Orang Tua Terhadap Hasil Belajar Teknik Televisi Jurusan Teknik Audeo Video SMKN 5 Padang - Forry Sudriati; Zulwisli Zulwisli; Zulkifli Naansyah (Universitas Negeri Padang, 2014)
This research is purposed to reveal scales of independent learning contribution and attention of parents grade for televisionengineering subject at X class Electronics engineering SMKN 5 Padang. The type of this research is descriptive correlation. Populations in this research are 74 students, and samples are amount to 43 students of X class Electronical engineering SMKN 5 Padang, school of year 2012/2013. Samples are taken by simple random sampling technique. Data were collected by questionnaire and documentation. Data analysis technique in this research is Pearson product moment and multiple-correlation. Results from data analysis claimed that there are contributions personal competence of teachers and how to study student’s for student’s grade of digital engineering subject at X class Electronics engineering SMKN 5 Padang, as follow: (1) independent learning gives contribution to student’s grade by 56,4%, (2) attention of parents gives contribution to student’s grade by 17,72%, (3) independent learningtogether with attention of parents contribution to student’s grade by 29,70%. This research suggest that student’s independent learning and attention of parents give contribution to student’s grade.Keywords:independent learning, attention of parents, student’s grade, descriptive correlation, simple random sampling.